Detection of Epstein-Barr virüs DNA by polymerase chain reaction in surgical specimens of patients with squamous celi carcinoma of the larynx and vocal cord nodules - Gök, Üzeyir; Keleş, Erol; Özdarendeli, Aykut; Bulut, Yasemin; Çobanoğlu, Bengü (İstanbul Üniversitesi, 2003)
Objectives: We investigated the incidence of Epstein- Barr virüs EBV infection in surgical specimens of squa- mous celi carcinoma of the larynx and vocal cord nodules.Patients and Methods: Formalin-fixed, paraffin-embedded tissue samples randomly selected from 22 patients with squamous celi carcinoma of the larynx 20 males, 2females; mean age 52 years and from 17 patients with vocal cord nodules 14 males, 3 females; mean age 38 years were examined by the polymerase chain reaction. The patients were assessed in terms of localization of the disease, smoking habits, duration of smoking, and the presence or absence of EBV DNA.Results : Twenty-one patients with laryngeal carcinoma and nine patients with vocal cord nodules were smokers.Polymerase chain reaction showed EBV DNA in 11 patients 50% with laryngeal carcinoma and in seven patients 41.2% with vocal cord nodules. No significant differences were found with respect to EBV DNA positivity, smoking habits, smoking period, the number of cigarettes consumed daily, localization of disease, and tumor stage p>0.05 .Conclusion: Epstein-Barr virüs does not seem to be directly associated with the pathogenesis of laryngeal squamous celi carcinoma, but its role in the etiology of laryngeal proliferative diseases needs more elucidation.

Amaç: Larenjeal skuamöz hücreli karsinom ve vokal kordnodüllerine ait cerrahi örneklerde Ebstein-Barr virüsüarafltırıldı. Hastalar ve Yöntemler: Rastgele seçim yöntemiyle skuamöz hücreli larenks kanseri olan 22 hastanın 20 erkek,2 kadın; ort. yafl 52 ve vokal kord nodülü olan 17 hastanın 14 erkek, 3 kadın; ort. yafl 38 formalin ve parafindebekletilen cerrahi doku örnekleri polimeraz zincir reaksiyonu yöntemiyle incelendi. Olgular, hastalığın yerleflim yeri,sigara içme alıflkanlığı, süresi ve miktarı ve EBV DNAvarlığı açısından değerlendirildi. Bulgular: Larenks kanserli olguların 21’inde, vokal kordnodüllü olguların dokuzunda sigara içme öyküsü vardı.Polimeraz zincir reaksiyonu ile, kanserli olguların 11’inde %50 , vokal kord nodüllü olguların yedisinde %41.2 EBV-DNA pozitifliği saptandı. Gruplar içinde EBV-DNAvarlığı, sigara içme alıflkanlığı, süresi, bir günde tüketilensigara sayısı, hastalığın yerleflimi ve tümör evresi bakımından anlamlı farklılık görülmedi p > 0 . 0 5 .Sonuç: Bulgularımız, larenjeal skuamöz hücreli karsinompatogenezi ile EBV arasında doğrudan iliflki olmadığınıgöstermektedir; ama larengeal proliferatif hastalıkların etyolojisindeki rolü daha fazla arafltırma gerektirmektedir
Skuamöz hücreli larenks kanseri ve vokal kord nodüllü hastaların cerrahi doku örneklerinde polimeraz zincir reaksiyonuyla Epstein-Barr virüsü DNA'sı araştırması